Derajat Kesehatan Jasmani dan Postur Siswa Sekolah di Makassar - Muhammad Nadjib Bustan; Ians Aprilo; Khairil Anwar (Media Kesehatan Masyarakat Indonesia, 2018)
The future of the physical health status of the Indonesian nation is determined by the degree of physicalfitnessess of the young generation. Therefore, it is important to know how the status of youth physical health bymeasuring the degree of physical fitness of school children. The purpose of this study was to determine the degreeof physical health of children through measurement of body height, nutritional status, and posture of school children.A cross-sectional studywas conducted by drawing samples from four primary schools and four first middleschools in Makassar City. The schoolchild population was represented by 252 students who received physical fitnesschecks, and 228 students received special posture tests using Formetric/Pedoscan. The results showed a highproportion of children short and very short (23.7%). The proportion of children with nutritional status of skinnyand very thin as much as 29,8% accompanied by obesity group and obese 42,1%. The state of posture (somatotype)was beyond the normal limit in the form of endomorph (body shape fat) 36.5% and ectomorph (body shapeskiny)as much as 25.4%. Spinal misalignment was characterized by 27.0% kyphosis, 21.9% lordosis, and 38.2% of scoliosis.In conclusion, school students still have low physical fitness and high spinal misalignment.